Contemporary Topics of Pneumonia 2017
DOI: 10.5772/intechopen.71609
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia: A Challenging Health Concern with the Climate Change

Abstract: Pneumonia is still a global health concern with high mortality rate, mainly among children under 5 years and adults over 65 years. In addition to pathogen virulence, immunoevasion capacity, and drug resistance ability, risk factors for the patient include aging, comorbidities, malnutrition, and all causes affecting the immune system. The extent to which environmental disorders affect the respiratory health is established for chronic diseases such as asthma, COPD, and cardiovascular diseases, but less is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
(58 reference statements)
1
4
0
1
Order By: Relevance
“…Minimum temperature was also positively associated with severe pneumonia, whereas maximum temperature had a negative association. The findings of this study are in agreement with those of other authors, who found that humidity and temperature are contributing factors to the occurrence of pneumonia [ 19 , 20 , 21 , 22 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Minimum temperature was also positively associated with severe pneumonia, whereas maximum temperature had a negative association. The findings of this study are in agreement with those of other authors, who found that humidity and temperature are contributing factors to the occurrence of pneumonia [ 19 , 20 , 21 , 22 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Of great importance to this study is the effect environmental factors on pneumonia occurrence. Seasonal, climatic, and weather conditions, which are affected by precipitation, humidity, and temperature, have been found to be associated with pneumonia occurrence and hospitalization [ 19 , 20 , 21 , 22 , 23 , 24 ]. The seasonal changes have also been found to contribute to the occurrence of particular pathogens, as more pneumonia cases are experienced in the cold months than in other seasons [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is stated that vicious cycles of positive feedback in which infectious diseases and poverty mutually reinforce each other can produce “poverty traps.” Poverty‐related conditions such as malnutrition and helminthic infections as well as lack of enough resources to access health services can aggravate the outcome of infectious diseases. Malnutrition predisposes to immunosuppression through lack of many elements or oligo‐elements such as zinc and copper, involved in the performance of various components of the immune system . Some studies confirm that epidemiological factors related to deprivation such as poverty and illiteracy are associated with an increased incidence of pneumonia in developing populations, but their impact on prognosis of CAP is not well‐understood and only an increase in pneumonia deaths in children under 5 years because of malnutrition related to poverty has been claimed .…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition predisposes to immunosuppression through lack of many elements or oligo-elements such as zinc and copper, involved in the performance of various components of the immune system. 20 Some studies confirm that epidemiological factors related to deprivation such as poverty and illiteracy are associated with an increased incidence of pneumonia in developing populations, 21 but their impact on prognosis of CAP is not well-understood and only an increase in pneumonia deaths in children under 5 years because of malnutrition related to poverty has been claimed. 20 In the present study, residence in remote rural areas, difficult access to medical facilities and illiteracy were not associated with poor outcome in CAP, but being in the lower economic class (as an indicator of poverty)…”
Section: Discussionmentioning
confidence: 99%
“…Le fait pour eux de poser un regard critique sur les échecs et les réussites du gouvernement congolais, les amène à informer le public sur l'efficacité de ses représentants et l'aider à exiger des comptes. 70 Les médias ont un mandat d'informer les citoyens sur les partis politiques et les candidats participant aux élections et leurs programmes. De cette manière, ils contribuent à la formation de l'opinion de l'électorat et à l'éducation des électeurs sur la manière d'exercer leurs votes.Les médias peuvent ainsi être un outil non seulement pour informer les électeurs sur les enjeux et les candidats, mais aussi pour véhiculer des renseignements de base sur la façon de voter ou sur l'objet du vote.…”
Section: Le Rôle Des Médias Dans La Période Préélectoraleunclassified